The Impacts Of Indigenous-Chinese Relations On Muslim-Christian Relations: Economic, Political, Social, Cultural, And Historical Analysis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT Tensions between the Muslims and the Christians have been high in the 90s. The tensions, this writer believes. are strongly confounded by ethnic prijudice beween the predominantly Muslim poor indigeneous and predominantly Christian wealthy chinese. Relaxing the just mentioned tensions, therefore, should precede any other attends to relax the tensions between the Muslims and the Christians. This writer proposes Malaysian model of affirmative programs for the Indegeneous to relax tension between the Indegeneous and the Christians, and therefore the Muslims and the. Christians